Respuesta :
Ans: Average rate of change of function = -1
Explanation:
The average rate of change of function f over the interval [tex]a \leq x \leq b[/tex] is given as:
=> Average rate of change of function = [tex] \frac{f(b) - f(a)}{b-a} [/tex] --- (A)
Since,
a = -3
b = 1
Given function = [tex]f(x) = - \frac{(x+2)^2}{2} +5[/tex]
Therefore,
[tex]f(b) = - \frac{(b+2)^2}{2} +5[/tex]
Since b = 1; therefore,
[tex]f(b) = f(1) = - \frac{(3)^2}{2} +5 = \frac{1}{2} [/tex]
[tex]f(a) = - \frac{(a+2)^2}{2} +5[/tex]
Since a = -3; therefore,
[tex]f(a) = f(-3) = - \frac{(-1)^2}{2} +5 = \frac{9}{2} [/tex]
Plug-in the values of f(a), f(b), a, and b in equation (A):
(A) => Average rate of change of function = [tex] \frac{ \frac{1}{2} - \frac{9}{2} }{1-(-3)}[/tex]
=> Ans: Average rate of change of function = -1
-i
Explanation:
The average rate of change of function f over the interval [tex]a \leq x \leq b[/tex] is given as:
=> Average rate of change of function = [tex] \frac{f(b) - f(a)}{b-a} [/tex] --- (A)
Since,
a = -3
b = 1
Given function = [tex]f(x) = - \frac{(x+2)^2}{2} +5[/tex]
Therefore,
[tex]f(b) = - \frac{(b+2)^2}{2} +5[/tex]
Since b = 1; therefore,
[tex]f(b) = f(1) = - \frac{(3)^2}{2} +5 = \frac{1}{2} [/tex]
[tex]f(a) = - \frac{(a+2)^2}{2} +5[/tex]
Since a = -3; therefore,
[tex]f(a) = f(-3) = - \frac{(-1)^2}{2} +5 = \frac{9}{2} [/tex]
Plug-in the values of f(a), f(b), a, and b in equation (A):
(A) => Average rate of change of function = [tex] \frac{ \frac{1}{2} - \frac{9}{2} }{1-(-3)}[/tex]
=> Ans: Average rate of change of function = -1
-i
Average rate of change= [ f(1)-f(-3) ] / [1-(-3) ]
Average rate of change= [ f(1)-f(-3) ] / (1+3)
Average rate of change= [ f(1)-f(-3) ] / (4)
x=1→f(1)=-1/2(1+2)^2+5
f(1)=-1/2(3)^2+5
f(1)=-1/2(9)+5
f(1)=-(1*9)/2+5
f(1)=-9/2+5
f(1)=(-9+2*5)/2
f(1)=(-9+10)/2
f(1)=1/2
x=-3→f(-3)=-1/2(-3+2)^2+5
f(-3)=-1/2(-1)^2+5
f(-3)=-1/2(1)+5
f(-3)=-(1*1)/2+5
f(-3)=-1/2+5
f(-3)=(-1+2*5)/2
f(-3)=(-1+10)/2
f(-3)=9/2
Average rate of change= [ f(1)-f(-3) ] / (4)
Average rate of change= [ 1/2-9/2 ] / (4)
Average rate of change= [ (1-9) /2 ] / (4)
Average rate of change= [ (-8) /2 ] / (4)
Average rate of change= (-4) / (4)
Average rate of change= -1
Answer: The average rate of change for the quadratic function from x=−3 to x = 1 is equal to -1
Average rate of change= [ f(1)-f(-3) ] / (1+3)
Average rate of change= [ f(1)-f(-3) ] / (4)
x=1→f(1)=-1/2(1+2)^2+5
f(1)=-1/2(3)^2+5
f(1)=-1/2(9)+5
f(1)=-(1*9)/2+5
f(1)=-9/2+5
f(1)=(-9+2*5)/2
f(1)=(-9+10)/2
f(1)=1/2
x=-3→f(-3)=-1/2(-3+2)^2+5
f(-3)=-1/2(-1)^2+5
f(-3)=-1/2(1)+5
f(-3)=-(1*1)/2+5
f(-3)=-1/2+5
f(-3)=(-1+2*5)/2
f(-3)=(-1+10)/2
f(-3)=9/2
Average rate of change= [ f(1)-f(-3) ] / (4)
Average rate of change= [ 1/2-9/2 ] / (4)
Average rate of change= [ (1-9) /2 ] / (4)
Average rate of change= [ (-8) /2 ] / (4)
Average rate of change= (-4) / (4)
Average rate of change= -1
Answer: The average rate of change for the quadratic function from x=−3 to x = 1 is equal to -1